Solve the following equation:-
![\frac{ \frac{2}{5}x + 3 }{ \frac{1}{3}x - 1 } = \frac{3}{5} \frac{ \frac{2}{5}x + 3 }{ \frac{1}{3}x - 1 } = \frac{3}{5}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Cfrac%7B2%7D%7B5%7Dx+%2B+3+%7D%7B+%5Cfrac%7B1%7D%7B3%7Dx++-+1+%7D++%3D++%5Cfrac%7B3%7D%7B5%7D+)
uttamsalunkhe671:
ok
Answers
Answered by
19
Step-by-step explanation:
» 2/5x+3= 3 (cross multiplication)
1/3x-1 5
» 5(2/3x+3)= 3(1/3x-1)
» 10/5x+15= 3/3x-3
» 2x+15= x-3
» 2x-x= -3-15
» x= -18
#BeBrainly~
•wanna be frnds?シ︎
Attachments:
![](https://hi-static.z-dn.net/files/dd6/423d6016b3d45691b631514d34d8433c.jpg)
Similar questions